Chemokine Biology - Basic Research and Clinical Application Vol. 2: Pathophysiology of Chemokines - Neote, Kuldeep; Letts, L. Gordon; Moser, Bernhard (Progress in Inflammation Research,, 2007)
Chemokines play an important role in recruiting inflammatory cells into tissues in response to infection and inflammation. They also play an important role in coordinating the movement of T-cells, B-cells and dentritic cells, necessary to generate an immune response (response to injury, allergens, antigens, invading microorganisms). They selectively attract leukocytes to inflammatory foci, inducing both cell migration and activation. They are involved in various diseases, like atherosclerosis, lung and skin inflammation, multiple sclerosis, or HIV. Volume 2 of this two-volume set discusses the pathophysiology of chemokines. It is divided into two parts: a) chemokines in animal disease models, and b) chemokines as drug targets. Together with volume 1, which discusses the immunobiology of chemokines, both volumes give a comprehensive overview of chemokine biology.